2023
DOI: 10.1093/nar/gkad152
|View full text |Cite
|
Sign up to set email alerts
|

PML and PML-like exonucleases restrict retrotransposons in jawed vertebrates

Abstract: We have uncovered a role for the promyelocytic leukemia (PML) gene and novel PML-like DEDDh exonucleases in the maintenance of genome stability through the restriction of LINE-1 (L1) retrotransposition in jawed vertebrates. Although the mammalian PML protein forms nuclear bodies, we found that the spotted gar PML ortholog and related proteins in fish function as cytoplasmic DEDDh exonucleases. In contrast, PML proteins from amniote species localized both to the cytoplasm and formed nuclear bodies. We also iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 99 publications
0
9
1
Order By: Relevance
“…The Plex9.1 enzyme is also capable of suppressing cGAS-STING (Mathavarajah et al, 2023); however, we did not observe significant changes in Plex9.1 expression during gar regeneration. Therefore, we sought to determine if Plex9.1 may be differentially regulated to influence cGAS-STING signaling in another biological process, such as aging.…”
Section: Plex9 Enzymes Have Elevated Expression In the Cardiac Tissue...contrasting
confidence: 91%
See 4 more Smart Citations
“…The Plex9.1 enzyme is also capable of suppressing cGAS-STING (Mathavarajah et al, 2023); however, we did not observe significant changes in Plex9.1 expression during gar regeneration. Therefore, we sought to determine if Plex9.1 may be differentially regulated to influence cGAS-STING signaling in another biological process, such as aging.…”
Section: Plex9 Enzymes Have Elevated Expression In the Cardiac Tissue...contrasting
confidence: 91%
“…For example, LINE-1 retroelements were recently shown to promote the SASP through the activation of cGAS-STING (De Cecco et al, 2019). Previously, we have demonstrated that Pml, Trex1, and Plex9.1 collectively suppress LINE retroelements in an exonucleaseindependent manner to limit cGAS activation (Mathavarajah et al, 2023).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations